THE ROLE OF THE SCHOOL PRINCIPLE IN THE IMPLEMENTATION OF CHARACTER EDUCATION IN CHILD-FRIENDLY SCHOOL - Sindi Ladya Baharizqi (Indonesian Journal of Elementary Teachers Education, 2023)
Child-friendly schools are schools that are based on children and learning processes that must be supported by positive, healthy and safe social, physical and emotional surroundings. SDN 1 Cigadung is a child-friendly pilot school in Kuningan District. This type of research is qualitative with a case study type. The purpose of this research is to find out the role of the school principal in the implementation of character education at SDN 1 Cigadung. The results of this study are 1) The role of the principal in the implementation of child-friendly schools at SDN 1 Cigadung. 2) Driving and inhibiting factors for the role of the principal in the implementation of child-friendly schools at SDN 1 Cigadung.